Experiencing accents: a Knight-Thompson speechworkʼ guide for acting in accent - Thompson, Philip (Professor of Drama); Seiple, Tyler; Caban, Andrea (Routledge, 2024)
"Experiencing Accents: A Knight-Thompson Speechworkʼ Guide for Acting in Accent presents a comprehensive and systematic approach to accent acquisition for actors. It lays out an accessible and effective set of tools, exercises, and theoretical frameworks grounded in current linguistic science, as well as more than two decades of teaching, actor training, and coaching developed by Knight-Thompson Speechworkʼ. This book dismantles the notions that accents exist on a spectrum of good and bad or that "neutral," "general," or "standard" can serve as ideals for speech. By de-centering elitist and authoritarian worldviews, it gives actors a path to mobilize their innate language abilities to acquire any accent, relying on descriptive and experiential knowledge. The innovative approach of the Four Ps - People, Prosody, Posture, and Pronunciation - builds cultural competence that honors accents as they exist in the world, increases the physical and perceptive skills of the actor, and provides a rich variety of applications to encourage fluid and embodied accent performance. Each of the Four Ps are investigated and practiced separately and then synthesized in the art of the performer, allowing actors to address the complexity of acting in accent through a deliberate and sequential layering of skills, rendering the final expression of their technique meticulously accurate and deeply authentic. Organized into 16 modules to correspond with a typical semester, Experiencing Accents is perfect for Theatre students in Voice, Speech, and Accents courses, along with working actors interested in improving their accent work"--